Sociodemographic disparities in COVID-19 seroprevalence across England in the Oxford RCGP primary care sentinel network. Issue 6 (June 2022) - Whitaker, Heather; Tsang, Ruby S.M.; Button, Elizabeth; Andrews, Nick; Byford, Rachel; Borrow, Ray; Hobbs, F.D. Richard; Brooks, Tim; Howsam, Gary; Brown, Kevin; Macartney, Jack; Gower, Charlotte; et al.
Highlights: We present a serological survey of COVID-19 infections in England. This study used sera collected alongside routine blood tests in primary care. Seropositivity was higher in younger age and in Black and Asian ethnicities. And also higher in major conurbations and in non-smokers. We found no difference by deprivation, sex or shielding recommendation. Summary: Objectives: To monitor changes in seroprevalence of SARS-CoV-2 antibodies in populations over time and between different demographic groups. Methods: A subset of practices in the Oxford-Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) sentinel network provided serum samples, collected when volunteer patients had routine blood tests. We tested these samples for SARS-CoV-2 antibodies using Abbott (Chicago, USA), Roche (Basel, Switzerland) and/or Euroimmun (Luebeck, Germany) assays, and linked the results to the patients' primary care computerised medical records. We report seropositivity by region and age group, and additionally examined the effects of gender, ethnicity, deprivation, rurality, shielding recommendation and smoking status. Results: We estimated seropositivity from patients aged 18-100 years old, which ranged from 4.1% (95% CI 3.1–5.3%) to 8.9% (95% CI 7.8–10.2%) across the different assays and time periods. We found higher Euroimmun seropositivity in younger age groups, people of Black and Asian ethnicity (compared to white), major conurbations, and non-smokers. We did not observe any significant effect by region, gender, deprivation, or shielding recommendation. Conclusions: Our results suggest that prior to the vaccination programme, most of the population remained unexposed to SARS-CoV-2.